Comparing the Effects of Analysis-of-Practice and Content-Based Professional Development on Teacher and Student Outcomes in Science - Roth, Kathleen J.; Wilson, Christopher D.; Taylor, Joseph A.; Stuhlsatz, Molly A. M.; Hvidsten, Connie (American educational research journal, 2019)
This study tests the influence of a video-based, analysis-of-practice professional development (PD) program on upper-elementary teachers' science content knowledge, pedagogical content knowledge, and teaching practice and on their students' achievement. Using a cluster-randomized experimental design, the study compares the outcomes for teachers in an analysis-ofpractice program with those of teachers in a content-deepening program. Mediational analyses explore the relationship between teacher outcomes and student learning. In comparison with the content-deepening PD program, the analysis-of-practice PD program significantly impacted teachers knowledge and practice. Mediation analyses revealed a strong relationship between teaching practice and student learning. The study advances the field beyond the currently accepted consensus model of effective PD toward an empirically tested model.